Fiscal Policy and Debt Management: A Narrative Review of Global Lessons - Lestari, Putri Ayu; Andika, Cruift (Moneta : Journal of Economics and Finance, 2025)
This narrative review investigates global practices and lessons learned regarding fiscal policy and public debt sustainability, aiming to identify institutional, structural, and strategic factors that influence long-term fiscal balance. The study draws upon peer-reviewed empirical studies, panel data analyses, and case studies sourced from Scopus, Google Scholar, and other academic databases, using keywords such as "fiscal policy," "public debt," "fiscal sustainability," and "debt analysis." Studies were selected based on inclusion criteria that focused on national-level fiscal management and policy effectiveness, with particular emphasis on comparative and empirical analyses. Findings indicate that high debt-to-GDP ratios reduce fiscal space and hinder governments' ability to respond effectively to economic crises. Structural vulnerabilities, including institutional weaknesses and income inequality, further aggravate the sustainability of public debt. Effective strategies identified include the adoption of fiscal rules, independent fiscal councils, tax system reforms, and long-term investments in infrastructure and innovation. Comparative perspectives show that Nordic countries and selected Asian nations have achieved greater fiscal discipline through integrated institutional and policy frameworks. This review underscores the urgent need for systemic reforms that prioritize transparency, policy coordination, and inclusive economic growth. Future research should explore tailored debt sustainability frameworks and assess the political economy dimensions of fiscal governance. The findings provide evidence-based insights for policymakers seeking sustainable pathways to manage public debt without compromising developmental goals.